Silica particle dispersion
By using a dispersion of spherical silica particles with a median particle size of 0.5 to 20 μm and a moderate specific surface area, combined with an organic thixotropic agent and an appropriate solvent, the silica particle dispersion was solved during the film making process. The problems of low particle protrusions and peel strength achieve better dispersion stability and improved performance of the resin composition.
Patent Information
- Application Number
- CN202380038964.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-17
AI Technical Summary
The existing silica particle dispersion is prone to particle protrusions during film making, and the peeling strength is low. Especially under the purpose of low dielectricization, when the particle surface area is reduced or the particle size is increased, the particle contact area increases, resulting in The peel strength is reduced.
A spherical silica particle dispersion is used, wherein the median particle size of the spherical silica particles is 0.5-20 μm, the specific surface area and the median particle size are 2.7-5.0 μm²/g, and it contains silane compounds and organic thixotropic agents. The solvent is water, hydrocarbons, etc., and the solid content concentration is 70%. The aggregate is removed through dispersion treatment and franchise, thereby improving the dispersion stability.
The particle protrusions in the resin composition are effectively suppressed, the peel strength is improved, the uniform dispersion of silica particles is ensured, and the molding and film forming properties of the resin composition are enhanced.
Smart Images

Figure BDA0005122673670000231
Abstract
Description
Technical Field
[0001] The present invention relates to a silica particle dispersion liquid in which silica particles are dispersed in a solvent. Background Art
[0002] Silica particles have been used in various applications such as electronic materials such as printed circuit boards and package wiring boards, optical materials such as lenses and optical films, functional materials such as catalysts and catalyst carriers, and pigments such as paints and cosmetics. For example, the low dielectric properties of silica particles have been used in electronic substrates.
[0003] Silica particles tend to aggregate when used in a dry powder state, and therefore are used in the form of a dispersion dispersed in a solvent such as water or a resin depending on the intended use, and various silica particle dispersions and slurries containing the silica particle dispersions have been proposed.
[0004] For example, Patent Document 1 proposes a paste for electronic materials, which comprises: a filler for electronic materials, which has a particle size of 100 nm to 2000 nm or a specific surface area of 2 m 2 / g~35m 2 / g, the amount of water generated when heated at 200℃ is per 1m 2 A silica particle material having a surface area of 40 ppm or less, which is surface-treated with a silane compound having a vinyl group, a phenyl group, a phenylamino group, an alkyl group having 4 or more carbon atoms, a methacryloyl group, or an epoxy group; and a liquid dispersion medium which contains substantially no water.
[0005] Patent document 2 proposes a coating liquid for forming an antireflective film, which is composed of silica hollow particles (A) having an average particle size (Dpa) in the range of 30 to 200 nm, silica solid particles (B) having an average particle size (Dpb) in the range of 5 to 80 nm, and a solvent, wherein the concentration (CA) of the silica hollow particles (A) is in the range of 0.2 to 8 wt % based on the solid content, the concentration (CB) of the silica solid particles (B) is in the range of 0.2 to 8 wt % based on the solid content, and the weight ratio (B / A) of the silica hollow particles (A) to the silica solid particles (B) is in the range of 0.25 to 4.
[0006] Patent Document 3 proposes a dispersion of silica particles containing silica particles having an average particle size of 5 to 40 nm and a ratio of hollow particles to the total number of hollow particles and solid particles (hollowness ratio) of 70% or more.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2020-097498
[0010] Patent Document 2: Japanese Patent Application Publication No. 2015-102666
[0011] Patent Document 3: Japanese Patent Application Publication No. 2018-123043 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] However, when the existing silica particle dispersion is included in the resin composition and film-formed, it is easy to cause the silica particles to protrude, the peel strength becomes low, and it is sometimes difficult to obtain the desired effect of the silica particles. In particular, when used for the purpose of low dielectric, if the surface area of the silica particles is reduced or the particle size is increased, low dielectric can be achieved, but the contact area between the particles becomes large, so the peel strength is easily reduced.
[0014] The present invention has been made in view of the above problems, and an object of the present invention is to provide a silica particle dispersion that suppresses protrusions of particles during film formation and improves peel strength.
[0015] Solutions for solving problems
[0016] The present invention relates to the following (1) to (9).
[0017] (1) A silica particle dispersion comprising: spherical silica particles and a solvent, wherein the median particle size d50 of the spherical silica particles is 0.5 to 20 μm, and the specific surface area A (m 2 The product of the median particle size d50 (μm) and the median particle size d50 (μm) is 2.7 to 5.0 μm·m 2 / g.
[0018] (2) The silica particle dispersion according to (1) above, wherein the specific surface area of the spherical silica particles is 0.1 to 10 m 2 / g.
[0019] (3) The silica particle dispersion according to (1) or (2) above, wherein the viscosity of the spherical silica particles measured by the following measurement method is 5000 mPa·s or less.
[0020] (Measurement method)
[0021] The silica particle dispersion was dried to obtain powdered spherical silica particles. 8 parts by mass of the obtained powdered spherical silica particles were mixed with 6 parts by mass of cooked linseed oil and kneaded at 2000 rpm for 3 minutes. The obtained kneaded product was measured by a rotational rheometer at a shear rate of 1 s -1 The measurement was performed for 30 seconds, and the viscosity at the time of 30 seconds was obtained.
[0022] (4) The silica particle dispersion according to any one of (1) to (3) above, further comprising a silane compound having at least one group selected from the group consisting of a vinyl group, a phenyl group, a phenylamino group, an alkyl group having 4 or more carbon atoms, a methacryloyl group, and an epoxy group.
[0023] (5) The silica particle dispersion according to any one of (1) to (4) above, further comprising an organic thixotropic agent.
[0024] (6) The silica particle dispersion according to any one of (1) to (5), wherein the solvent contains at least one selected from the group consisting of water, hydrocarbons, alcohols, acetates, ketones, cellosolves, glycol ethers, chlorinated hydrocarbons and polar solvents.
[0025] (7) The silica particle dispersion according to any one of (1) to (6), wherein the viscosity of the silica particle dispersion at 25° C. when the solid content concentration of the spherical silica particles is 70% by mass is 20 to 20,000 mPa·s.
[0026] (8) A resin composition comprising the silica particle dispersion according to any one of (1) to (7) above.
[0027] (9) A method for producing a silica particle dispersion, wherein a solvent and a silica particle having a median particle size d50 of 0.5 to 20 μm and a specific surface area A (m 2 The product of the median particle size d50 (μm) and the median particle size A×d50 is 2.7 to 5.0 μm·m 2 / g of spherical silica particle powder is mixed, the mixed solution is dispersed and classified, and aggregates of the spherical silica particles are removed.
[0028] Effects of the Invention
[0029] Since the silica particle dispersion of the present invention has spherical silica particles uniformly dispersed in the liquid without agglomeration, particle protrusions can be suppressed when a resin composition containing the silica particle dispersion of the present invention is formed into a film, and peel strength can be improved. DETAILED DESCRIPTION
[0030] The present invention will be described below, but the present invention is not limited to the examples in the following description. It should be noted that in the present specification, "to" indicating a numerical range means that the numerical values described before and after it are included as the lower limit and the upper limit.
[0031] In addition, in this specification, "mass" and "weight" have the same meaning.
[0032] <Silica particle dispersion>
[0033] The silica particle dispersion of the present invention comprises spherical silica particles and a solvent, wherein the spherical silica particles have a median particle size d50 of 0.5 to 20 μm and a specific surface area A (m 2 The product of the particle size (A×d50) and the median particle size (μm) is 2.7 to 5.0 μm·m 2 The spherical silica particles in the silica particle dispersion of the present invention are uniformly dispersed without aggregation, and the dispersion stability of the spherical silica particles in the dispersion is improved, and protrusions of the particles when the spherical silica particles are included in a resin composition and formed into a film can be suppressed, and the peel strength can be improved.
[0034] (Solvent)
[0035] The solvent used as the dispersion medium of the silica particle dispersion can be arbitrarily selected according to the purpose of use, and examples thereof include water, hydrocarbons, alcohols, acetates, ketones, cellosolves, glycol ethers, chlorinated hydrocarbons, and polar solvents. The solvent preferably contains at least one selected from the group consisting of these.
[0036] Examples of hydrocarbons include toluene, methylcyclohexane, n-heptane, and m-xylene. Examples of alcohols include ethanol, isopropanol, 1-propanol, isobutanol, 1-butanol, and 2-butanol. Examples of acetates include propyl acetate, isobutyl acetate, and butyl acetate. Examples of ketones include methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Examples of cellosolves include ethylene glycol monomethyl ether and ethylene glycol monoethyl ether. Examples of glycol ethers include 1-methoxy-2-propanol, 1-methoxypropyl-2-acetate, 1-ethoxy-2-propanol, and 3-ethoxyethyl propionate. Examples of chlorinated hydrocarbons include trichloroethylene and tetrachloroethylene. Examples of polar solvents include N-methyl-2-pyrrolidone.
[0037] The solvent may be appropriately selected depending on the intended field of use. For example, when used for an insulating layer of a wiring board of an electronic device, ketones and hydrocarbons are preferably used, and specifically, methyl ethyl ketone (MEK), toluene, and the like are preferably used.
[0038] In addition, when the silica particle dispersion of the present invention is used in a curable composition, a liquid main agent and a curing agent itself can be used as a solvent. As the aforementioned main agent, for example, epoxy resin, polyphenylene ether resin, polyester resin, polyimide resin, phenolic resin, o-divinylbenzene resin, etc. can be cited, and as the curing agent, for example, polyamine curing agents, acid anhydride curing agents, phenolic curing agents, active ester curing agents, peroxides, etc. can be cited.
[0039] The solvent is preferably contained in the silica particle dispersion in a range of 15 to 90% by mass. If the content of the solvent is 15% by mass or more, the spherical silica particles can be uniformly dispersed, and the viscosity of the dispersion does not become excessively high, so it is easy to handle. In addition, if the content of the solvent is 90% by mass or less, it is in a liquid state, so it can be used directly in a dispersed state. The content of the solvent in the silica particle dispersion is more preferably 20% by mass or more, further preferably 25% by mass or more, particularly preferably 30% by mass or more, and most preferably 40% by mass or more. In addition, it is more preferably 85% by mass or less, further preferably 80% by mass or less, and particularly preferably 75% by mass or less.
[0040] (Spherical silica particles)
[0041] Spherical silica particles are solid silica with a median particle size d50 of 0.5 to 20 μm and a specific surface area A (m 2 The product of the particle size (A×d50) and the median particle size (g) is between 2.7 and 5.0 μm·m 2 / g(2.7≤A×d50(μm·m 2 / g)≤5.0).
[0042] The following physical properties of the spherical silica particles can be confirmed by drying the silica particle dispersion to obtain powdered silica particles.
[0043] If the median particle size d50 of the spherical silica particles is in the above range, it is a viscosity that is easy to handle, and it is not easy to form particle protrusions during coating. Therefore, when used as a resin composition, the peel strength of the resin composition is appropriately maintained. In addition, if the median particle size becomes excessively large, the value of the fineness meter becomes large. Therefore, when the resin composition containing spherical silica particles is made into a film such as a sheet, the minimum thickness of the sheet becomes thicker. Therefore, in the present invention, the median particle size d50 of the spherical silica particles is set to a range of 0.5 to 20 μm. The median particle size d50 is preferably greater than 1 μm, and the upper limit is preferably less than 10 μm, more preferably less than 5 μm.
[0044] The median diameter d50 is determined using a laser diffraction particle size distribution measuring apparatus (for example, "MT3300EXII" manufactured by Microtrac BEL Corp.).
[0045] The specific surface area A of the spherical silica particles is preferably 0.1 to 10 m 2 / g range. If the specific surface area is 0.1m 2 / g or more, when the spherical silica particles are contained in the resin composition, the contact points with the resin are sufficient, so the compatibility with the resin becomes good. In addition, if it is 10m 2 / g or less, the dielectric loss tangent can be reduced, and the dispersibility in the resin composition is improved. The specific surface area A is more preferably 8m 2 / g or less, more preferably 7m 2 / g or less, particularly preferably 5m 2 It should be noted that it is difficult to obtain a specific surface area A of less than 0.1 m 2 / g.
[0046] The specific surface area is determined by a BET method based on a nitrogen adsorption method using a specific surface area and pore distribution measuring apparatus (for example, “BELSORP-miniII” manufactured by Microtrac BELCorp., “TriStar II” manufactured by Micromeritics, etc.).
[0047] Moreover, the specific surface area A (m 2 The product of the particle size (A×d50) and the median particle size (μm) is 2.7 to 5.0 μm·m 2 / g, preferably 2.7 to 4.5 μm·m 2 / g, more preferably 2.7 to 4.0 μm·m 2 / g. The theoretical value of A×d50 is 2.7 [based on the specific surface area = 6 / (the true density of silica is 2.2 (g / m 3 )×median diameter d50 (μm))], values below this are not realistically achievable. If the value of A×d50 is 5.0μm·m 2 / g or less, the specific surface area per unit particle size becomes smaller, and the dielectric loss tangent can be reduced.
[0048] The sphericity of the spherical silica particles is preferably 0.75 to 1.0. If the sphericity is too low, the contact area of the member with which the silica particles in the resin layer in the resin composition containing the silica particle dispersion contact decreases, and the peel strength may decrease. Therefore, the sphericity is preferably 0.75 or more.
[0049] The sphericity is expressed by measuring the maximum diameter (DL) and the short diameter (DS) orthogonal to the maximum diameter (DL) of any 100 particles in a projected image taken using a scanning electron microscope (SEM), and calculating the average value of the ratio (DS / DL) of the minimum diameter (DS) to the maximum diameter (DL).
[0050] From the viewpoint of dispersibility and the like, the sphericity is more preferably 0.90 or more, further preferably 0.93 or more, and the closer to 1.0 the more preferred.
[0051] The spherical silica particles preferably have a viscosity of 5000 mPa·s or less as measured by the following measurement method.
[0052] (Measurement method)
[0053] The silica particle dispersion was dried to obtain powdered spherical silica particles. 8 parts by mass of the obtained powdered spherical silica particles were mixed with 6 parts by mass of cooked linseed oil and kneaded at 2000 rpm for 3 minutes. The obtained kneaded product was measured by a rotational rheometer at a shear rate of 1 s -1 The measurement was performed for 30 seconds, and the viscosity at the time of 30 seconds was obtained.
[0054] The shear rate 1s of the kneaded material determined by the above measurement method -1 If the viscosity is below 5000mPa·s, it can be said that the silica particles are dense, and the peel strength when forming the resin composition can be improved. In addition, reducing the amount of solvent added during the molding and film-forming of the resin composition containing spherical silica particles can speed up the drying speed and improve productivity. In addition, if the specific surface area corresponding to the particle size of the silica particles becomes larger, the viscosity becomes easy to increase when added to the resin composition, but the specific surface area of the spherical silica particles is small, therefore, the viscosity of the resin composition can be suppressed. The viscosity of the kneaded product is more preferably below 4000mPa·s, and further preferably below 3500mPa·s.
[0055] The shear rate of the above-mentioned mixture is 1s -1 The lower the viscosity, the better the coating property of the resin composition and the better the productivity, so the lower limit is not particularly limited.
[0056] The dielectric loss tangent of the powder of spherical silica particles is preferably less than 0.0020, more preferably less than 0.0010, and further preferably less than 0.0008 at a frequency of 1 GHz. In particular, in the determination of the dielectric loss tangent and dielectric constant of the powder, when the frequency is above 10 GHz, the sample space becomes smaller and the measurement accuracy deteriorates. Therefore, the measured value at a frequency of 1 GHz is adopted in the present invention. If the dielectric loss tangent of the spherical silica particles at a frequency of 1 GHz is less than 0.0020, an excellent dielectric loss suppression effect is obtained, and therefore, a substrate and a sheet with improved high-frequency characteristics are obtained. The smaller the dielectric loss tangent, the more the transmission loss of the circuit is suppressed, and therefore, the lower limit is not particularly limited.
[0057] The dielectric loss tangent can be measured by a perturbation resonator method using a dedicated device (for example, "Vector Network Analyzer E5063A" manufactured by KEYCOM Corp.).
[0058] The 3746 cm-1 emanates from the isolated silanol groups on the surface of spherical silica particles. -1 The IR peak intensity near is preferably 0.1 or less, more preferably 0.08 or less, and further preferably 0.06 or less. An isolated silanol group refers to a silanol group (Si-OH) group that is not bonded to water or the like adsorbed on the silica particles. The amount of isolated silanol groups (Si-OH) on the surface of the silica particles is obtained by IR measurement. Specifically, the IR spectrum is measured at 800 cm -1 Normalized at 3800cm -1 After aligning the baselines, find 3746cm -1 If there are many isolated silanol groups on the particle surface, the dielectric loss tends to increase when the component mixed with the resin is used for electronic applications. However, the 3746cm peak intensity of the isolated silanol groups on the particle surface is -1 If the IR peak intensity in the vicinity is 0.1 or less, the dielectric loss can be reduced.
[0059] In addition, the silanol groups bonded to the surface of the spherical silica particles are located at 3300-3700 cm -1 The maximum IR peak intensity is preferably 0.2 or less, more preferably 0.17 or less, and further preferably 0.15 or less. The bonded silanol group refers to a silanol (Si-OH) group bonded to water adsorbed on the silica particles, silanol on the silica surface, etc. The amount of bonded silanol (Si-OH) groups on the surface of the silica particles is obtained by IR measurement. Specifically, the IR spectrum is measured at 800 cm -1 Normalized at 3800cm -1 After the baseline is aligned, the -1The relative value of the peak intensity of the bonded Si-OH group is calculated from the maximum peak in the graphene. If there are many bonded silanol groups on the particle surface, the dielectric loss tends to increase when the component mixed with the resin is used for electronic purposes. However, the peak intensity of the bonded silanol groups originating from the particle surface is located at 3300-3700cm -1 If the maximum IR peak intensity is 0.2 or less, the dielectric loss can be reduced.
[0060] Spherical silica particles are preferably non-porous particles. If they are porous particles, the oil absorption becomes large, the viscosity in the resin increases, the surface area increases, the amount of silanol (Si-OH) groups on the surface of the silica particles increases, and there is a tendency for the dielectric loss tangent to deteriorate. Specifically, the oil absorption is preferably 100ml / 100g or less, more preferably 70ml / 100g or less, and most preferably 50ml / 100g or less. The lower limit is not particularly limited, and it is substantially difficult to make the oil absorption less than 20ml / 100g.
[0061] The spherical silica particles contain titanium (Ti) in an amount of preferably 30 to 1500 ppm, more preferably 100 to 1000 ppm, and even more preferably 100 to 500 ppm.
[0062] Ti is an arbitrary component contained in the manufacture of spherical silica particles. When spherical silica particles are manufactured, when fine powder is generated due to the rupture of silica particles, the fine powder will adhere to the surface of the mother particles, and the specific surface area of the particles will increase. By including Ti when manufacturing spherical silica particles, it becomes easy to perform hot compaction during firing. As a result, it becomes difficult to break during post-treatment after firing, so the generation of fine powder can be suppressed, and the attached particles attached to the surface of the mother particles of silica can be reduced, thereby suppressing the increase in specific surface area. By including more than 30ppm of Ti, hot compaction is easy to perform during firing, so the generation of fine powder caused by rupture can be suppressed. If the Ti content is less than 1500ppm, the above-mentioned effect is obtained while suppressing the increase in the amount of silanol groups, and the deterioration of the dielectric loss tangent can be suppressed.
[0063] The spherical silica particles may contain impurity elements other than titanium (Ti) within a range that does not impair the effects of the present invention. Examples of the impurity elements include Na, K, Mg, Ca, Al, and Fe in addition to Ti.
[0064] The total content of alkali metals and alkaline earth metals in the impurity elements is preferably 2000 ppm or less, more preferably 1000 ppm or less, and further preferably 200 ppm or less.
[0065] The spherical silica particles may be treated with a silane coupling agent.
[0066] The surface of the spherical silica particles is treated with a silane coupling agent, thereby reducing the amount of residual silanol groups on the surface, making the surface hydrophobic, inhibiting water adsorption, improving dielectric loss, and improving affinity with resin when forming a resin composition, thereby improving dispersibility and strength of the resin film after forming.
[0067] The surface treatment conditions are not particularly limited, and general surface treatment conditions may be used, and a wet treatment method or a dry treatment method may be used. From the viewpoint of performing a uniform treatment, a wet treatment method is preferred.
[0068] Examples of the silane coupling agent include aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, and organic silazane compounds. The silane coupling agent may be used alone or in combination of two or more.
[0069] Specifically, examples of the silane coupling agent include aminopropylmethoxysilane, aminopropyltriethoxysilane, ureidopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, N-2 (aminoethyl) aminopropyltrimethoxysilane and other aminosilane coupling agents; glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, glycidyloxypropylmethyldiethoxysilane, glycidylbutyltrimethoxysilane, (3,4-epoxycyclohexyl)ethyltrimethoxysilane and other epoxysilane coupling agents; mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane and other mercaptosilane coupling agents; methyltrimethoxysilane, vinyltrimethoxysilane, octadecyltrimethoxysilane and other epoxysilane coupling agents. Silane coupling agents such as trimethoxysilane, phenyltrimethoxysilane, methacryloxypropyltrimethoxysilane, imidazole silane, triazine silane, CF3(CF2)7CH2CH2Si(OCH3)3, CF3(CF2)7CH2CH2SiCl3, CF3(CF2)7CH2CH2Si(CH3)(OCH3)2, CF3(CF2)7CH2CH2Si(CH3)C12, CF3(CF2)5CH2CH2SiCl3, CF3(CF2)5CH2CH2Si(OCH3)3, CF3CH2CH2SiCl3, CF3CH2CH2Si(OCH3)3, C8F 17 SO2N(C3H7)CH2CH2CH2Si(OCH3)3, C7F 15 CONHCH2CH2CH2Si(OCH3)3、C8F 17 CO2CH2CH2CH2Si(OCH3)3、C8F 17-O-CF(CF3)CF2-O-C3H6SiCl3, C3F7-O-(CF(CF3)CF2-O)2-CF(CF3)CONH-(CH2)3Si(OCH3)3 and other fluorine-containing silane coupling agents, hexamethyldisilazane, hexaphenyldisilazane, trisilazane, cyclotrisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane and other organic silazane compounds, etc.
[0070] The amount of the silane coupling agent attached is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and further preferably 0.10 parts by mass or more, and more preferably 5 parts by mass or less, and further preferably 2 parts by mass or less, based on 100 parts by mass of the spherical silica particles.
[0071] Whether the surface of the spherical silica particles has been treated with a silane coupling agent can be confirmed by detecting a peak generated by a substituent of the silane coupling agent by IR. The amount of the silane coupling agent attached can be measured by the amount of carbon.
[0072] The spherical silica particles are preferably contained in the silica particle dispersion in a range of 10 to 85% by mass. If the content of the spherical silica particles is 10% by mass or more, the desired peel strength can be imparted with a small amount of the silica particle dispersion added to the resin composition. If it is 85% by mass or less, the viscosity of the dispersion does not increase excessively and it is easy to handle. The content of the spherical silica particles in the silica particle dispersion is more preferably 15% by mass or more, further preferably 20% by mass or more, particularly preferably 25% by mass or more, and more preferably 80% by mass or less, further preferably 75% by mass or less, particularly preferably 70% by mass or less, and most preferably 60% by mass or less.
[0073] (Silane compound)
[0074] The silica particle dispersion of the present invention preferably contains a silane compound having at least one group selected from the group consisting of a vinyl group, a phenyl group, a phenylamino group, an alkyl group having more than 4 carbon atoms, a methacryloyl group, and an epoxy group. By containing the aforementioned silane compound, when the silica particle dispersion is contained in the resin composition, the surface of the spherical silica particles is compatible with the resin, thereby further improving the peel strength of the resin composition. It should be noted that when the spherical silica particles are treated with a silane coupling agent, it is not necessarily necessary to add a silane compound.
[0075] As the aforementioned silane compound, for example, vinyl silane, phenyl silane, phenyl amino silane, hexyl silane, decyl silane, 3-methacryloxypropyl trimethoxy silane, aminopropyl silane, etc. can be cited. They can be used alone or in combination of two or more. Among them, from the viewpoint of interaction with the resin, preferably a silane compound comprising vinyl, phenyl, methacryloyl, epoxy or phenyl amino, more preferably a silane compound comprising vinyl, phenyl, methacryloyl or phenyl amino, further preferably a silane compound comprising phenyl or methacryloyl. In this case, the dispersibility of the silica particles in the mixed product described later and the silica particle dispersion of the present invention is improved, and its viscosity is particularly easy to maintain a balance with the peel strength of the molded product formed therefrom.
[0076] The silane compound is preferably contained in the silica particle dispersion in a range of 0.01 to 5% by mass. If the content of the silane compound is 0.01% by mass or more, the compatibility of the spherical silica particles and the resin is improved when the silica particle dispersion is contained in the resin composition, and the peel strength of the resin composition can be improved. If it is 5% by mass or less, the residue in the composition is suppressed, and the effect on the physical properties of the resin composition can be reduced. The content of the silane compound in the silica particle dispersion is more preferably 0.02% by mass or more, further preferably 0.04% by mass or more, and particularly preferably 0.05% by mass or more. In addition, it is more preferably 4% by mass or less, and particularly preferably 3% by mass or less.
[0077] (Organic Thixotropic Agent)
[0078] The silica particle dispersion of the present invention preferably further contains an organic thixotropic agent.
[0079] The organic thixotropic agent is added to suppress aggregation and precipitation of spherical silica particles in the silica particle dispersion and the resin composition or slurry containing the silica particle dispersion, and to improve wettability of the flux to the cured product of the resin composition or slurry.
[0080] Examples of organic thixotropic agents include fatty acid amides (amide waxes) synthesized from vegetable oil fatty acids and amines; surfactants such as fatty acid esters, polyethers, sulfated oils, and higher alcohol sulfates; polycarboxylates; polycarboxylic acid amides; and urea-modified compounds, but excluding hydrogenated castor oil waxes, which are known as castor oil waxes, and oxidized polyethylene waxes, which are waxes in which polar groups are introduced by oxidation of polyethylene. The organic thixotropic agent may be used alone or in combination of two or more.
[0081] The organic thixotropic agent can be obtained as a commercial product, for example, BYK (registered trademark) -R606, BYK (registered trademark) -405, BYK (registered trademark) -R605, BYK (registered trademark) -R607, BYK (registered trademark) -410, BYK (registered trademark) -411, BYK (registered trademark) -415, BYK (registered trademark) -430, BYK (registered trademark) -431, BYK (registered trademark) -7410ET, BYK (registered trademark) -7411ES (all manufactured by BYK Japan Co., Ltd.), Talen 1450, Talen 2000, Talen 2200A, Talen 7200-20, Talen 8200-20, Talen 8300-20, Talen 8700-20, Talen BA-600, Flownon SH-290, Flownon SH-295S, Flownon SH-350, Flownon HR-2, Flownon HR-4AF (all manufactured by Kyoeisha Chemical Co., Ltd.).
[0082] The organic thixotropic agent is preferably contained in the silica particle dispersion in the range of 0.01 to 5 mass %. If the content of the organic thixotropic agent is 0.01 mass % or more, the aggregation of the spherical silica particles in the dispersion is suppressed, and when the silica particle dispersion is contained in the resin composition, the resin can be suppressed from accumulating between the spherical silica particles. Thus, the peel strength of the resin composition is improved. In addition, if the content of the organic thixotropic agent is 5 mass % or less, the residue in the composition is suppressed, and the influence on the physical properties of the resin composition can be reduced. The content of the organic thixotropic agent in the silica particle dispersion is more preferably 0.02 mass % or more, further preferably 0.04 mass % or more, particularly preferably 0.05 mass % or more, and more preferably 4 mass % or less, further preferably 3 mass % or less, particularly preferably 2.5 mass % or less.
[0083] The silica particle dispersion of the present invention may contain other optional components within the range not impairing the effects of the present invention. Examples of the optional components include other inorganic fillers such as alumina, and curing compositions.
[0084] (Physical Properties of Silica Particle Dispersion)
[0085] The silica particle dispersion of the present invention preferably has a viscosity of 20 to 20,000 mPa·s at 25° C. when the solid content concentration of the spherical silica particles is 70% by mass.
[0086] If the viscosity of the silica particle dispersion at 25°C in which the solid content concentration of the spherical silica particles is 50% by mass is 20 mPa·s or more, the sedimentation (floating) separation of silica can be prevented, and if it is 20000 mPa·s or less, the silica can be used while being maintained in a dispersed state. The above-mentioned viscosity is more preferably 50 mPa·s or more, further preferably 75 mPa·s or more, particularly preferably 100 mPa·s or more, and most preferably 500 mPa·s or more, and more preferably 15000 mPa·s or less, further preferably 12000 mPa·s or less, and particularly preferably 10000 mPa·s or less.
[0087] <Method for producing silica particle dispersion>
[0088] The silica particle dispersion of the present invention is obtained by dispersing powder of spherical silica particles in a solvent. The spherical silica particles can be obtained by production, or commercially available spherical silica particles can be used.
[0089] Hereinafter, a method for producing spherical silica particles and a method for producing a silica particle dispersion using the spherical silica particles will be described.
[0090] (Method for producing spherical silica particles)
[0091] As a method for producing spherical silica particles, a method of forming a spherical silica precursor by a wet method and obtaining spherical silica particles from the precursor can be cited. The wet method refers to a method including a process of obtaining a raw material of spherical silica particles by using a liquid as a silica source and gelling it. By using the wet method, spherical silica particles can be formed, so there is no need to adjust the shape of the particles by crushing, etc., and as a result, particles with a small specific surface area are obtained. In addition, in the wet method, it is not easy to generate particles that are significantly smaller than the average particle size, and the specific surface area tends to become smaller after firing. In addition, in the wet method, by adjusting the impurities of the silica source, the amount of impurity elements such as titanium can be adjusted, and then a state in which the aforementioned impurity elements are uniformly dispersed in the particles can be formed.
[0092] As a wet method, for example, a spray method, an emulsion gelation method, etc. can be cited. As an emulsion gelation method, for example, a dispersed phase and a continuous phase containing a silica precursor are emulsified, and the obtained emulsion is gelled to obtain a spherical silica precursor. As an emulsification method, the following method is preferably used: the dispersed phase containing a silica precursor is supplied to the continuous phase by means of a micropore portion or a porous membrane to prepare an emulsion. Thus, an emulsion with a uniform droplet diameter is prepared, and as a result, a spherical silica with a uniform particle size is obtained. As such an emulsification method, a micromixer method and a membrane emulsification method are used. For example, the micromixer method is disclosed in International Publication No. 2013 / 062105.
[0093] The pore volume of the spherical silica precursor obtained by the wet method is expected to be 0.3 to 2.2 ml / g. If the pore volume of the silica precursor is 0.3 ml / g or more, the silica particles will fully shrink during firing, and the specific surface area can be reduced. The pore volume of the silica precursor is preferably 0.3 ml / g or more, more preferably 0.6 ml / g or more, and further preferably 0.7 ml / g or more. In addition, if the pore volume of the silica precursor is 2.2 ml / g or less, the input bulk density before firing is suppressed from becoming excessively large, and productivity can be improved. The pore volume of the silica precursor is preferably 2.2 ml / g or less, more preferably 1.8 ml / g or less, and most preferably 1.5 ml / g or less.
[0094] The pore volume is determined by the BJH method based on a nitrogen adsorption method using a specific surface area and pore distribution measuring apparatus (for example, “BELSORP-miniII” manufactured by Microtrac BEL Corp., “TriStar II” manufactured by Micromeritics, etc.).
[0095] The ignition loss of the silica precursor obtained by the wet method is expected to be 5.0 to 15.0 mass%. The ignition loss is the sum of the attached water attached to the silica precursor and the water produced by the condensation of the silanol groups contained in the silica precursor. The silica precursor has a moderate silanol group, so that the condensation is promoted during firing, and the silanol group becomes easy to reduce. If the ignition loss is too much, the yield during firing is reduced and the productivity deteriorates. Therefore, the ignition loss of the silica precursor is preferably 15.0 mass% or less, more preferably 13.0 mass% or less, and most preferably 12.0 mass% or less. If the ignition loss is too little, the silanol group becomes easy to remain during firing, so the ignition loss of the silica precursor is preferably 5.0 mass% or more, more preferably 6.0 mass% or more, and most preferably 7.0 mass% or more.
[0096] Here, the ignition loss is determined as the mass loss when 1 g of the silica precursor is heat-dried at 850° C. for 0.5 hours in accordance with JIS K0067.
[0097] The spherical silica particles are obtained by heat treating the aforementioned spherical silica precursor. During the heat treatment, the spherical silica particles are sintered to densify the shell while reducing the amount of silanol groups on the surface and lowering the dielectric loss tangent. The heat treatment temperature is preferably above 700°C, more preferably above 800°C, and most preferably above 900°C. In addition, if the temperature becomes excessively high, the particles become easy to aggregate and the fineness in the resin composition becomes larger. Therefore, it is preferably below 1600°C, more preferably below 1500°C, and most preferably below 1400°C. That is, it is preferred to perform heat treatment in the range of 700 to 1600°C.
[0098] The method of the heat treatment is not particularly limited, and examples thereof include heat treatment by a static method, heat treatment by a rotary kiln method, and heat treatment by spray combustion.
[0099] The spherical silica particles obtained by the above steps may aggregate in the drying and calcining steps. Therefore, they may be crushed to obtain an aggregate diameter that is easy to handle. However, in the present invention, they are directly mixed with a solvent to obtain a silica particle dispersion.
[0100] Examples of the crushing method include a method using a mortar, a method using a dry or wet ball mill, a method using an oscillating sieve, a method using a crusher such as a pin mill, a cutter mill, a hammer mill, a knife mill, a roller mill, or a jet mill.
[0101] In this manner, the spherical silica particles used in the silica particle dispersion of the present invention are obtained.
[0102] (Preparation of Silica Particle Dispersion Liquid)
[0103] The obtained spherical silica particles are mixed with a solvent to obtain a silica particle dispersion. The method for producing a silica particle dispersion of the present invention comprises the following steps: mixing a solvent with a powder of spherical silica particles, dispersing and classifying the mixed solution, and removing aggregates of the spherical silica particles. The spherical silica particles used have a median particle size d50 of 0.5 to 20 μm and a specific surface area A (m 2 The product of the particle size (A×d50) and the median particle size (μm) is 2.7 to 5.0 μm·m 2 The type and amount of the solvent and other physical properties of the spherical silica particles are as described above.
[0104] The powder of spherical silica particles is preferably mixed in a silica particle dispersion at a ratio of 10 to 85% by mass. If the ratio of the spherical silica particles is too small, the productivity of the subsequent concentration process decreases. In addition, if it is too much, the viscosity of the silica particle dispersion sometimes increases excessively, and the productivity of the dispersion treatment decreases. Therefore, the range of 10 to 85% by mass is preferred. The amount of spherical silica particles is more preferably 15% by mass or more, further preferably 20% by mass or more, particularly preferably 25% by mass or more, and more preferably 80% by mass or less, further preferably 75% by mass or less, particularly preferably 70% by mass or less, and most preferably 60% by mass or less.
[0105] The mixed solution containing the solvent and the spherical silica particles can be dispersed using a dispersion device used for pigment dispersion or the like. For example, mixers such as dispersers, homomixers, and planetary mixers, homogenizers (such as "CLEAR mix" manufactured by MTechnique Co., Ltd., "FILMIX" manufactured by PRIMIX, and "Abramix" manufactured by Silverson, etc.), paint mixers (manufactured by Red Devil, Inc.), colloid mills (such as "PUC colloid mill" manufactured by PUC, and "Colloid Mill MK" manufactured by IKA), cone mills (such as "Cone Mill MKO" manufactured by IKA), ball mills, sand mills (such as "Dyno-mill" manufactured by SHINMARU ENTERPRISES CORPORATION), attritors, bead mills (such as "DCP mill" manufactured by Eirich), media dispersers such as co-ball mills, wet jet mills (such as "Genas PY" manufactured by Genas, "Star-burst" manufactured by Suginos Machine Limited, and "Nanomizer" manufactured by Nanomizer, etc.), MTechnique Co., Ltd. "CLEAR SS-5", Nara Machinery Manufacturing Co., Ltd. "MICROS" and other media-free dispersers, as well as roller mills, kneading machines, etc. Among them, it is desirable not to use pulverizing media (balls, beads, etc.). This is because, if pulverizing media is used, there is a concern about the contamination of the worn media. Specifically, it is ideal to use a wet jet mill (Genas "Genas PY", Suginos Machine Limited "Star-burst", Nanomizer "Nanomizer", etc.), M Technique Co., Ltd. "CLEAR SS-5", Nara Machinery Manufacturing Co., Ltd. "MICROS" and other media-free dispersers.
[0106] In addition, the temperature during the dispersion treatment is preferably 0 to 100°C. The temperature during the dispersion treatment here refers to the temperature range before and after the treatment. By performing the dispersion treatment within the aforementioned temperature range, the viscosity of the solvent is appropriately maintained, productivity is maintained, and the evaporation of the solvent is suppressed, and the solid content can be easily controlled. The treatment temperature is more preferably 5°C or more, and more preferably 10°C or more, and more preferably 90°C or less, and more preferably 80°C or less.
[0107] The time for the dispersion treatment can be appropriately set according to the dispersion apparatus used so that particle destruction does not proceed, and is preferably 0.5 to 60 minutes, more preferably 0.5 to 10 minutes, and further preferably 0.5 to 5 minutes.
[0108] Afterwards, the aggregates of the spherical silica particles that are not completely dispersed and remain after the dispersion treatment are wet classified. Wet classification can include classification based on a sieve or centrifugal force. When a sieve is used, it is preferred to use a sieve with an opening of less than 100 μm for classification. As the sieve, for example, a metal with a dense grid-like structure such as an electroformed sieve is preferably used.
[0109] The opening of the sieve is preferably 100 μm or less, more preferably 75 μm or less, further preferably 50 μm or less, and particularly preferably 35 μm or less. In addition, the lower limit of the opening of the sieve is preferably 0.2 μm or more, more preferably 0.5 μm or more, and further preferably 1 μm or more. That is, the opening of the sieve is preferably in the range of 0.2 to 100 μm.
[0110] Thereafter, the solution may be diluted or concentrated as necessary to adjust the concentration to an appropriate level. Examples of the concentration method include gasification concentration and solid-liquid separation.
[0111] It should be noted that in the method for producing a silica particle dispersion of the present invention, a silane coupling agent may be added to the mixed solution of the solvent and the spherical silica particles. Examples of the silane coupling agent include the above-mentioned silane coupling agents.
[0112] <Resin composition>
[0113] The silica particle dispersion of the present invention can be mixed with a resin and used as a resin composition. The resin composition preferably contains spherical silica particles in an amount of 5 to 70% by mass, more preferably 10 to 50% by mass.
[0114] As resin, one or more of epoxy resin, silicone resin, phenolic resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamideimide, polyetherimide, etc., polyesters such as polybutylene terephthalate and polyethylene terephthalate, polyphenylene sulfide, aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber / styrene) resin, AES (acrylonitrile / ethylene / propylene / diene rubber-styrene) resin, polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE), etc. can be used. The dielectric loss tangent in the resin composition also depends on the characteristics of the resin, so these selected resins can be considered.
[0115] The resin composition may contain an optional component other than the above-mentioned resin and medium. Examples of the optional component include a dispersing aid, a surfactant, and a filler other than silica.
[0116] It should be noted that when the resin film is made of the resin composition of the present invention, its dielectric loss tangent is preferably 0.012 or less, more preferably 0.010 or less, and further preferably 0.009 or less at a frequency of 10 GHz. If the dielectric loss tangent of the resin film at a frequency of 10 GHz is 0.012 or less, the electrical properties are excellent, and therefore, it can be expected that it will be used in electronic equipment, communication equipment, etc. The smaller the dielectric loss tangent, the more the transmission loss of the circuit is suppressed, and therefore, the lower limit is not particularly limited.
[0117] The dielectric loss tangent can be measured using a separated dielectric resonator (SPDR) (for example, manufactured by Agilent Technologies).
[0118] In addition, the average linear expansion coefficient of the resin film is preferably 10 to 50 ppm / °C. When the average linear expansion coefficient is within the above range, it is close to the range of the thermal expansion coefficient of copper foil widely used as a substrate, and therefore the electrical properties are excellent. The average linear expansion coefficient is more preferably 12 ppm / °C or more, and further preferably 15 ppm / °C or more, and more preferably 40 ppm / °C or less, and further preferably 30 ppm / °C or less.
[0119] The average linear expansion coefficient is determined as follows: using a thermomechanical analyzer (e.g., "TMA-60" manufactured by Shimadzu Corporation), the above-mentioned resin film is heated at a load of 5N and a heating rate of 2°C / min, the dimensional change of the sample from 30°C to 150°C is measured, and the average is calculated to determine the average linear expansion coefficient.
[0120] The silica particle dispersion of the present invention can be used as various filling materials, and is particularly suitable for use as a filling material for a resin composition used in the preparation of electronic substrates used in electronic devices such as personal computers, notebook computers, digital cameras, and communication devices such as smart phones and game consoles. Specifically, the silica particle dispersion of the present invention can also be expected to be applied to resin compositions, prepregs, metal foil-clad laminates, printed circuit boards, resin sheets, adhesive layers, adhesive films, solder resists, bump reflows, rewiring insulating layers, chip bonding materials, sealing materials, underfills, mold underfills, and stacked inductors, etc., with low dielectric loss tangent, low transmission loss, low moisture absorption, and improved peel strength.
[0121] Example
[0122] Hereinafter, the present invention will be described in detail based on Examples, but the present invention is not limited thereto. In the following description, the same substances are used for common components.
[0123] In addition, Examples 1 to 7 are Examples, and Examples 8 to 10 are Comparative Examples.
[0124] <Test Example 1>
[0125] In Test Example 1, spherical silica particles were prepared and a silica particle dispersion using the obtained spherical silica particles was prepared.
[0126] (Example 1)
[0127] Silica powder 1 (AGC-Si-Tech Co., Ltd.: H-31, d50 = 3.5 μm) produced by a wet method was used as a spherical silica precursor. 150 g of silica powder 1 was filled in an alumina crucible and heated at 1200° C. in an electric furnace for 1 hour. After the heating treatment, the mixture was cooled to room temperature and ground with an agate mortar to obtain spherical silica powder as an aggregate of spherical silica particles.
[0128] 100 g of the obtained spherical silica powder and 43 g of methyl ethyl ketone (MEK) were placed in a 250 ml plastic bottle and stirred at 30 rpm for 2 hours using a mixing rotor. The obtained mixed solution was subjected to a wet micronizing device (STAR BURST MINI manufactured by SUGINO MACHINE LIMITED, model number: HJP-25001) from The slurry was discharged from a nozzle at a pressure of 100 MPa, and this operation was repeated three times. The obtained slurry was passed through an electroforming mesh with an opening of 10 μm to obtain a silica particle dispersion having a solid content of 70% by mass.
[0129] (Example 2)
[0130] A silica particle dispersion was obtained by performing the same treatment as in Example 1 except that a silica powder 2 produced by a wet method (AGC-Si-Tech Co., Ltd.: H-51, d50=5.5 μm) was used as a spherical silica precursor.
[0131] (Example 3)
[0132] A silica particle dispersion was obtained by performing the same treatment as in Example 1 except that a silica powder 3 produced by a wet method (AGC-Si-Tech Co., Ltd.: H-121, d50=13 μm) was used as a spherical silica precursor and the slurry was passed through an electroforming sieve with an opening of 30 μm.
[0133] (Example 4)
[0134] A silica particle dispersion was obtained by performing the same treatment as in Example 1 except that a silica powder 4 produced by a wet method (AGC-Si-Tech Co., Ltd.: H-201, d50=20 μm) was used as a spherical silica precursor and the slurry was passed through an electroforming sieve with an opening of 40 μm.
[0135] (Example 5)
[0136] In a 250 ml plastic bottle, 100 g of the spherical silica powder obtained in Example 4, 43 g of methyl ethyl ketone (MEK), and 0.10 g of KBM-503 (3-methacryloxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) were placed and stirred at 30 rpm for 2 hours using a mixing rotor. The resulting mixed solution was heated at 80° C. for 1 hour, cooled, and then pulverized using a wet micronizer (STAR BURST MINI manufactured by SUGINO MACHINE LIMITED, model number: HJP-25001). The slurry was passed through an electroforming sieve with an opening of 10 μm to obtain a silica particle dispersion having a solid content of 70% by weight.
[0137] (Example 6)
[0138] In a 250 ml plastic bottle, 100 g of the spherical silica powder obtained in Example 4, 43 g of methyl ethyl ketone (MEK), and 0.10 g of BYK (registered trademark)-R606 (polyhydroxycarboxylic acid ester, manufactured by BYK Corporation) were placed and stirred at 30 rpm for 2 hours using a mixing rotor. The resulting mixed solution was subjected to a wet micronizing device (STAR BURSTMINI manufactured by SUGINO MACHINE LIMITED, model number: HJP-25001) from The slurry was discharged from a nozzle at a pressure of 100 MPa, and this operation was repeated three times. The obtained slurry was passed through an electroforming mesh with an opening of 10 μm to obtain a silica particle dispersion having a solid content of 70% by mass.
[0139] (Example 7)
[0140] In Example 5, a silica particle dispersion was obtained in the same manner as in Example 5 except that KBM-503 was changed to 0.10 g of KBM-103 (trimethoxyphenylsilane, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0141] (Example 8)
[0142] Spherical silica powder 5 (manufactured by Denka Company Limited: FB-5D) made from raw silica produced by a dry process was used. 150 g of spherical silica powder 5 was filled in an alumina crucible and heated at 1300° C. in an electric furnace for 1 hour. After the heating treatment, the mixture was cooled to room temperature and ground with an agate mortar to obtain spherical silica powder. The obtained spherical silica powder was used to obtain a silica particle dispersion in the same manner as in Example 1.
[0143] (Example 9)
[0144] A silica particle dispersion was obtained in the same manner as in Example 1 using spherical silica powder 6 (manufactured by Admatechs: SC-04) produced from raw silica produced by the VMC method.
[0145] (Example 10)
[0146] 10 g of the spherical silica powder obtained in Example 4 was used as it is.
[0147] In addition, the specific surface area, median particle size, viscosity of the kneaded product, and viscosity of the 70 mass % dispersion of the spherical silica powder prepared in the above examples were measured as follows and the results are shown in Table 1.
[0148] 1. Specific surface area
[0149] The spherical silica particles were dried under reduced pressure at 230° C. to completely remove moisture to prepare a sample. The specific surface area of the sample was determined by the multipoint BET method using nitrogen gas using an automatic specific surface area and pore distribution measuring apparatus “TriStar II” manufactured by Micromeritics.
[0150] 2. Median particle size
[0151] The median diameter was measured using a laser diffraction particle size distribution measuring device (MT3300EXII manufactured by MicrotracBEL Corp.). Ultrasonic waves were irradiated three times for 60 seconds in the device to disperse the spherical silica particles and measure the median diameter. The measurement was performed twice, each for 60 seconds, and the average value was calculated.
[0152] 3. Viscosity of the mixture
[0153] 6 parts by mass of cooked linseed oil (manufactured by Sankei Sangyo Co., Ltd.) and 8 parts by mass of spherical silica particles were mixed and kneaded at 2000 rpm for 3 minutes using a deaerator (bubble mixer) (manufactured by THINKY CORPORATION) which is a rotary and revolving mixer to prepare a kneaded product. -1 The kneaded product was measured for 30 seconds at room temperature to determine the viscosity at 30 seconds. It should be noted that the viscosity measured using only boiled linseed oil was 46 mPa·s.
[0154] 4. Viscosity of silica particle dispersion
[0155] 42 g of spherical silica particles and 18 g of methyl ethyl ketone (MEK) (solid content concentration 70% by mass) were placed in a 100 ml plastic bottle and stirred at 30 rpm for 2 hours using a mixing rotor. The resulting mixed solution was subjected to a wet micronizer (STAR BURST MINI manufactured by SUGINOMACHINE LIMITED, model number: HJP-25001) from The slurry was sprayed out from a nozzle at a pressure of 50 MPa, and this operation was repeated 3 times. The obtained slurry was adjusted to 25°C, and its viscosity was measured for 30 seconds at a shear rate of 1 rpm using a rotational rheometer (modular rheometer Physica MCR-301 manufactured by Antonpaar), and the viscosity at the time of 30 seconds was obtained.
[0156] <Test Example 2>
[0157] (Preparation of Evaluation Sample A (Resin Film))
[0158] The silica particle dispersions of Examples 1 to 9 and the spherical silica powder of Example 10 were used to prepare resin films.
[0159] 25 parts by mass of a biphenyl epoxy resin (epoxy equivalent 276, "NC-3000" manufactured by Nippon Kayaku Co., Ltd.) was heated and dissolved in 13 parts by mass of methyl ethyl ketone (MEK) while stirring. After cooling to room temperature, 32 parts by mass of an active ester curing agent ("HP8000-65T" manufactured by DIC Corporation, active group equivalent 223, toluene solution of 65% by mass of nonvolatile components) was mixed therein, and kneaded at 2000 rpm for 5 minutes using a deaerator stirrer, and 0.9 parts by mass of 4-dimethylaminopyridine (DMAP) as a curing accelerator and 1.6 parts by mass of 2-ethyl-4-methylimidazole ("2E4MZ" manufactured by Shikoku Chemical Industry Co., Ltd.) were mixed, and mixed at 2000 rpm for 5 minutes using a homodisper. The silica particle dispersion or spherical silica powder was weighed and mixed therein so as to obtain 90 parts by mass of particle powder, and the mixture was mixed at 2000 rpm for 5 minutes using a homodispersor.
[0160] Next, a release-treated transparent polyethylene terephthalate (PET) film ("PET5011 550" manufactured by LINTEC, 50 μm thick) was prepared. The obtained varnish was applied to the release-treated surface of the PET film using an applicator so that the thickness after drying was 40 μm, and then dried in a Gill aging thermostat at 100°C for 10 minutes and cut to produce an uncured laminated film having an uncured product (B-stage film) of a resin film of 200 mm in length × 200 mm in width × 40 μm in thickness.
[0161] The obtained uncured laminated film was heated in a Gill oven set at 190° C. for 90 minutes to cure the uncured material of the resin film, thereby producing a cured film.
[0162] (Preparation of Evaluation Sample B (Laminate))
[0163] (1) Lamination process
[0164] A single-sided roughened copper foil (F0-WS, thickness 18 μm, surface roughness Rz = 1.2 μm, manufactured by Furukawa Electric Co., Ltd.) was prepared. The uncured laminated film prepared above was laminated on the copper foil in such a manner that the surface of the uncured resin film (B-stage film) and the roughened surface of the copper foil were facing each other using the "intermittent vacuum laminator MVLP-500-IIA" manufactured by Meiki Seisakusho Co., Ltd., to obtain a laminated structure formed by copper foil / B-stage film / PET film. The lamination conditions were set as follows: decompression for 30 seconds to make the air pressure below 13 hPa, and then pressurization for 30 seconds at 100°C and a pressure of 0.8 MPa.
[0165] (2) Film peeling process
[0166] The PET film of the laminated structure was peeled off.
[0167] (3) Curing process
[0168] The laminate was placed in a Gill aging thermostat with an internal temperature of 180° C. for 30 minutes to cure the B-stage film and form an insulating layer.
[0169] (evaluate)
[0170] 1. Determination of peel strength
[0171] For evaluation sample B, a strip cut with a width of 1 cm was formed on the copper foil side. The substrate was mounted on a 90° peel tester, and the edge of the copper plating layer with the cut was grasped with a gripper, and the copper plating layer was peeled off by 20 mm to measure the peel strength (N / cm).
[0172] 2. Particle protrusions in the coating
[0173] The appearance of the uncured laminated film was observed and the particle protrusions of the coating film were evaluated. The evaluation criteria were as follows. It should be noted that the evaluations of A and B were judged to be practical.
[0174] [Evaluation Criteria]
[0175] A (good): No particle protrusions.
[0176] B (acceptable): Fine irregularities were visible after coating.
[0177] C (unacceptable): Streaks due to adhesion of coarse particles were observed during coating.
[0178] The above test results are collectively shown in Table 1.
[0179] [Table 1]
[0180] Table 1
[0181]
[0182] As shown in Table 1, Examples 1 to 7 have higher peel strength and stronger adhesive force than Examples 8 to 10. In addition, the coatings of Examples 1 to 7 also have good particle protrusions, which are suitable for practical use. In contrast, Examples 8 to 10 have lower peel strengths and particle protrusions are also visible in the coatings.
[0183] The present invention is described in detail and with reference to specific embodiments, but it is obvious to those skilled in the art that various changes and modifications may be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2022-077093) filed on May 9, 2022, and its contents are incorporated herein by reference.
Claims
1. A silica particle dispersion, comprising: spherical silica particles and a solvent, wherein the median particle size d50 of the spherical silica particles is 0.5 to 20 μm, and the specific surface area A (m 2 The product of the median particle size d50 (μm) and the median particle size d50 (μm) is 2.7 to 5.0 μm·m 2 / g.
2. The silica particle dispersion according to claim 1, wherein The specific surface area of the spherical silica particles is 0.1 to 10 m 2 / g.
3. The silica particle dispersion according to claim 1 or 2, wherein The viscosity of the spherical silica particles measured by the following measurement method is 5000 mPa·s or less, (Measurement method) The silica particle dispersion was dried to obtain powdered spherical silica particles. 8 parts by mass of the obtained powdered spherical silica particles were mixed with 6 parts by mass of cooked linseed oil and kneaded at 2000 rpm for 3 minutes. The obtained kneaded product was measured by a rotational rheometer at a shear rate of 1 s -1 The measurement was performed for 30 seconds, and the viscosity at the time of 30 seconds was obtained. 4 . The silica particle dispersion according to claim 1 , further comprising a silane compound having at least one group selected from the group consisting of a vinyl group, a phenyl group, a phenylamino group, an alkyl group having 4 or more carbon atoms, a methacryloyl group, and an epoxy group. 5 . The silica particle dispersion according to claim 1 , further comprising an organic thixotropic agent.
6. The silica particle dispersion according to any one of claims 1 to 5, wherein The solvent includes at least one selected from the group consisting of water, hydrocarbons, alcohols, acetates, ketones, cellosolves, glycol ethers, chlorinated hydrocarbons, and polar solvents.
7. The silica particle dispersion according to any one of claims 1 to 6, wherein The viscosity of the silica particle dispersion at 25° C. when the solid content concentration of the spherical silica particles is 70% by mass is 20 to 20,000 mPa·s. 8 . A resin composition comprising the silica particle dispersion according to claim 1 .
9. A method for producing a silica particle dispersion, wherein: The solvent and the median particle size d50 are 0.5 to 20 μm and the specific surface area A (m 2 The product of the median particle size d50 (μm) and the median particle size d50 (μm) is 2.7 to 5.0 μm·m 2 / g of spherical silica particle powder is mixed, the mixed solution is dispersed and classified, and aggregates of the spherical silica particles are removed.
Citation Information
Patent Citations
Porous silica particles and method for producing same
CN111527047A
Resin composition, resin film, and metal-clad laminate
CN112745676A
Dispersible silica NANO hollow particles and method for producing dispersion liquid of silica NANO hollow particles
JP2009107857A
Surface-treated silica powder, slurry composition, and resin composition using the same
JP2015036357A
Fluorine resin sheet, laminate, and manufacturing method therefor
JP2019183005A
